2020
DOI: 10.1037/cdp0000283
|View full text |Cite
|
Sign up to set email alerts
|

Racial-ethnic differences in social networks and perceived support: Measurement considerations and implications for disparities research.

Abstract: Background & Method Statistical Analyses & Results Conclusions Structural Support Social Network Index (SNI) • Number of people in one's network: NHBs reported significantly less people in their networks than NHWs: b=-1.69*, t(2690) =-2.89, p = .004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Black people report fewer friends than Whites, but do not differ in feeling adequately supported ( 338 ). Findings on racial differences in family support vary ( 338 , 339 ). It is plausible in theory that social support could contribute to the Black-White disparity in PTB.…”
Section: Findings From the Review Including Comments On The Plausibil...mentioning
confidence: 99%
“…Black people report fewer friends than Whites, but do not differ in feeling adequately supported ( 338 ). Findings on racial differences in family support vary ( 338 , 339 ). It is plausible in theory that social support could contribute to the Black-White disparity in PTB.…”
Section: Findings From the Review Including Comments On The Plausibil...mentioning
confidence: 99%
“…These findings are not unique to this sample as studies have consistently found that African Americans have a lower socioeconomic status, 33 are less likely to get married and more likely to get divorced, 34 and report smaller social networks and lower perceived social support. 35 Although these factors did not impact the within group differences (cCBT vs UC) in outcomes observed in our primary analyses, all of these sociodemographic factors have been found to play a role in physical and mental health. 33,36 Thus, future programs to address health disparities likely need to consider that impact of social determinants of poor health and not simply implementing treatments that focus on the readily addressable, surface-level, mental health concerns.…”
Section: Discussionmentioning
confidence: 58%
“…This is a concern. Flores et al (2020), for example, examined the social networks and social support structures of diverse samples. Whereas non-Hispanic White and Hispanic respondents had similar networks and support structures, non-Hispanic Blacks tended to have poorer supports.…”
Section: Discussionmentioning
confidence: 99%